Implementasi Evakuasi Mengangkat dan Menindahkan Pasien Cedera (Lifting and Moving) Pada Kader Tangguh Bencana di Desa Sempu - Setyowati, Anis (STIKES dan AKZI Karya Husada Kediri, 2025)
The prevalence of injuries in Indonesia in 2018 was 9.2%, this prevalence increased compared to previous years. First aid is very important for people who are injured, because this first aid greatly influences their subsequent condition, whether they recover, become disabled or die. Help can be done by lifting and moving injured patients. Lifting and moving injured patients cannot be done haphazardly, so training needs to be carried out. The aim of this activity is to improve the abilities and skills of disaster resilient cadres in carrying out evacuations, lifting and moving (Lifting and Moving) injured patients. This activity was carried out in Sempu village, Wates sub-district, Kediri district, the training participants were a cadre of 33 people, carried out in Sempu village, for 7 days, with details of the planning stage starting from 14-17 October 2024, implementation starting from 26-27 October 2024 , and the monitoring and evaluation stage on November 2 2024. The results of this activity were that the maximum age range was >35 years as many as 20 cadres (60.6%), the majority gender is female, 18 cadres (54.55%), the majority education is high school/equivalent, 24 cadres (72.7%), and the majority of jobs are in the private sector, 21 cadres (63.6%). The training carried out on cadre knowledge increased to a good number of 31 cadres, and skills also increased to 31 cadres (93.94%) cadres who were skilled in providing living and moving assistance to injured patients. This shows that this training activity was successful in increasing knowledge and skills of disaster resilient cadres in Sempu village, Wates sub-district, Kediri district.